235k views
5 votes
If f(x) = 3x - 2 and g(x) = 2x + 1, find (f+ g(x).

O A. 5x-3
O B. x-1
O c. x-3
O D. 5x-1
SUBMIT
Plzzz helpp

User Hostnik
by
5.3k points

2 Answers

3 votes

Answer:

(f+g)(x)=5x-1

Explanation:

To find (f+g)(x), add f(x) and g(x)

f(x)+g(x)

We know that f(x) is equal to 3x-2 and g(x) equals 2x+1.

f(x)=3x-2

g(x)=2x+1

(3x-2)+ (2x+1)

Combine like terms. Add all the terms with a variable, then all the terms without a variable

(3x+2x)+(-2+1)

5x+(-2+1)

5x-1

(f+g)(x)=5x-1

User Lincr
by
5.9k points
2 votes

Answer:

5x-1

Explanation:

f(x) = 3x - 2

g(x) = 2x + 1

f(x) + g(x) = 3x-2 +2x+1

Combine like terms

= 5x-1

User Robert Apikyan
by
5.3k points